Religious Pluralism (Perspective of Islamic Normativity and History) - Hamzah, Ekawati (Journal of Islam and Science, 2020)
This paper discusses "Normative and Historical Perspective Religious Pluralism, which includes two main problems, namely: First, how is religious pluralism in a historical perspective. Second, how is religious pluralism with a normative perspective. Religious pluralism in the perspective of revelation (Normative) is not only part of a humanitarian task but also a dimension of the Muslim’s level, devotion and a religious duty which is the value of worship in the sight of Allah SWT. Whereas historically, the religious attitude in the midst of a plural society was exemplified by the Prophet in the early days of Islam, so that in its development it became the religion that most respected the values of plurality. Therefore, in its development, Muslims do not need to feel a dilemma if in their life they have to intersect with other religions, instead they must be used as life partners in facing the benefit of the people.